PENGEMBANGAN KONSEP BETON RAMAH LINGKUNGAN PADA SELF COMPACTING CONCRETE (SCC) MENGGUNAKAN BOTTOM ASH DAN SIKACIM CONCRETE - Rudi, Rudi; Amran, Yusuf; Oktavia, Chica (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2025)
Self-Compacting Concrete (SCC) is an innovative type of concrete that can compact itself without the need for a vibrator, thus improving casting efficiency and concrete quality. This study aims to analyze the effect of using bottom ash as a partial replacement for fine aggregates and the addition of Sikacim Concrete on the physical and mechanical properties of SCC. Bottom ash is derived from the waste of the Tarahan coal-fired power plant, while Sikacim Concrete serves as a superplasticizer to improve workability. The mix variations consist of 0%, 25%, and 50% bottom ash and 1.25% Sikacim Concrete. Compressive strength tests were conducted at the ages of 1, 3, 5, and 7 days. The results show that the mixture with 25% bottom ash and 1.25% Sikacim Concrete provided the optimum results at all ages tested. At 1 day, the compressive strength reached 26.233 MPa, an increase from the control concrete which was 19.265 MPa. At 3 days, the highest compressive strength was 33.232 MPa. At 5 days and 7 days, the compressive strength reached 27.571 MPa and 28.718 MPa, respectively, both higher than the control concrete. Conversely, the use of 50% bottom ash led to a decrease in compressive strength at all ages due to a reduction in workability and concrete compaction. Thus, the combination of 25% bottom ash and 1.25% Sikacim Concrete proved effective in improving compressive strength and casting efficiency, as well as being environmentally friendly. This mixture is recommended as an innovative alternative in the development of modern concrete technology while supporting the use of industrial waste as a sustainable construction material